2015
DOI: 10.1016/j.neurobiolaging.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic responding during movie-watching predicted by age differences in attentional control

Abstract: Much is known about how age affects the brain during tightly controlled, though largely contrived, experiments, but do these effects extrapolate to everyday life? Naturalistic stimuli, such as movies, closely mimic the real world and provide a window onto the brain's ability to respond in a timely and measured fashion to complex, everyday events. Young adults respond to these stimuli in a highly synchronized fashion, but it remains to be seen how age affects neural responsiveness during naturalistic viewing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
98
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 61 publications
12
98
1
1
Order By: Relevance
“…Head motion was significantly lower during movie watching (Campbell et al, 2015) relative to resting state, SNG, and Cattell tasks ( F = 14.44, p < 0.001), which is consistent with previous reports showing that individuals are more compliant during movie watching (Vanderwal et al, 2015). Moreover, head motion across the three cognitive states (resting state, movie watching, and Cattell task) was highly correlated with head motion during SNG ( r = 0.81, p < 0.001) and did not interact with age ( F = 1.84, p = 0.139).…”
Section: Resultssupporting
confidence: 91%
“…Head motion was significantly lower during movie watching (Campbell et al, 2015) relative to resting state, SNG, and Cattell tasks ( F = 14.44, p < 0.001), which is consistent with previous reports showing that individuals are more compliant during movie watching (Vanderwal et al, 2015). Moreover, head motion across the three cognitive states (resting state, movie watching, and Cattell task) was highly correlated with head motion during SNG ( r = 0.81, p < 0.001) and did not interact with age ( F = 1.84, p = 0.139).…”
Section: Resultssupporting
confidence: 91%
“…A well‐suited paradigm for this purpose is the viewing of a naturalistic movie (Campbell et al, 2015; Hasson, Malach, & Heeger, 2010). By correlating a given regional time course of activity across subjects, a measure of response homogeneity can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…A well-suited paradigm for this purpose is the viewing of a naturalistic movie (Campbell et al, 2015;Hasson, Malach, & Heeger, 2010).…”
mentioning
confidence: 99%
“…First, resting state scans are relatively easy to obtain and particularly well suited to special populations, such as children and others who may have difficulty performing experimental tasks in the scanner. While it is debatable whether older individuals fall into this category, and recent work has shown that naturalistic viewing paradigms (such as movie-watching) may be better suited to special populations as they increase compliance and minimize head motion in the scanner (Vanderwal, Kelly, Eilbott, Mayes, & Castellanos, 2015; Campbell et al, 2015), resting state runs certainly minimize the demands placed on elderly participants. Further, because there is no specific task to perform at rest, group differences in functional connectivity are thought to reflect intrinsic or unbiased differences in underlying network organization, rather than group differences in response to the task itself (although this assumption will be called into question below).…”
mentioning
confidence: 99%